The pseudepigrapha and Christian origins essays from the Studiorum Novi Testamenti Societas - Oegema, Gerbern S. 1958-; Charlesworth, James H. 1940-; Society for New Testament Studies (New York [u.a.] T & T Clark, 2008)
A seminar chaired from 2000 to 2006 by professors James H. Charlesworth and Gerbern S. Oegema have met five times in various locations
Ancient Bible manuscripts and the biblical canon Lee Martin McDonald.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Apocryphal books -- Criticism, interpretation, etc -- Congresses; Christianity -- Origin -- Congresses; Church History -- Primitive and early church, ca. 30-600 -- Sources -- Congresses; Apocryphal books -- Criticism, interpretation, etc. -- Congresses; Christianity -- Origin -- Congresses; Church History -- Primitive and early church, ca. 30-600 -- Sources -- Congresses; Konferenzschrift; Aufsatzsammlung